Craniofacial morphology in Chinese and Swedish children with Angle Class I and Class II occlusal relations - Zeng Xiang-Long; Forsberg Carl-Magnus; Linder-Aronson Sten (Australasian Orthodontic Journal, 1998)
The purpose of this study was to compare the craniofacial morphology of a group of Chinese children from northern China with a group of Swedish children. Each ethnic group comprised 20 boys and 20 girls with Class I occlusion, and 20 boys and 20 girls with Class II occlusion. The ages of the children ranged from eight to ten years. Lateral cephalometric radiographs were used for the recording of a number of skeletal, dental, nasopharyngeal airway, and hyoid bone variables. The results of the comparisons of the two ethnic groups showed that the antero-posterior dimensions of the anterior cranial base and the maxilla in the Chinese children were significantly smaller than the corresponding dimensions in the Swedish children. The mean values of anterior and posterior face heights, inclination of the upper incisors, and protrusion of the lower incisors, were significantly greater in the Chinese than in the Swedish samples. In the median piane, the size of the nasopharyngeal airway was significantly greater in the Chinese than in the Swedes. This difference was due to the fact that the soft tissues covering the posterior nasopharyngeal wali were thinner in the Chinese children than in the Swedish children. In generał, the ethnic differences were the same in the Class I and the Class II groups. The differences in some of the dental and skeletal characteristics found between northern Chinese and Caucasian children are similar to previously described differences between southern Chinese and Caucasian children.